Analisis Perbandingan Kinerja Keuangan Bank Umum BUMN Dan Bank Umum Swasta Yang Terdaftar Di Bursa Efek Indonesia Tahun 2011 - 2015 - Hotman Fredy; Yetty Murni; Muhidin (Fakultas Ekonomi Dan Bisnis Universitas Pancasila, 2017)
The purpose of this research is to determine whether there are significant differences in the CAR, NPL, ROA, ROE, NIM, BOPO, and LDR between government bank compared to private banks in Indonesia Stock Exchange (IDX) the periode of 2011-2015. Method of sample selection was done by purposive sampling, the samples obtained from government banks such as BNI, BRI, BTN, and Mandiri bank, while from private banks such as BCA, CIMB Niaga, Danamon, and Permata bank. Data analysis methods is hypothesis testing using two different test mean (paired sample t-test) and wilcoxon signed rank test. The results showed that the financial performance of the ratio for CAR, NPL, ROA, NIM, BOPO, and LDR there is no significant difference between the government banks and private bank. While the financial performance of the ROE ratio there are significant differences between the government banks and private banks